2018
DOI: 10.1111/jfbc.12518
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antidiabetic activity of hydrolyzed peptides derived fromJuglans mandshuricaMaxim. fruits in insulin-resistant HepG2 cells and type 2 diabetic mice

Abstract: Bioactive peptides derived from plant proteins are promising sources for the development safe hypoglycemics. The present study was designed to investigate the antidiabetic activity of walnut hydrolyzed peptides (WHPs) obtained from the fruit proteins of Juglans mandshurica Maxim. In vitro results showed that WHPs with medium molecular weights (3-10 kDa) exhibited the highest a-glucosidase inhibitory rate (61.73%) and significantly increased extracellular glucose consumption in insulin-resistant HepG2 cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The α-glucosidase inhibition assays were carried out according to the method described by Wang et al (2018b). Briefly, 5 µL of α-glucosidase solution (1.0 U/ mL), 20 µL of WSE, and 165 µL of sodium phosphate buffer (0.1 mM, pH 6.8) were mixed and incubated in a 96-well plate at 37°C for 10 min.…”
Section: α-Amylase and α-Glucosidase Inhibitory Activitiesmentioning
confidence: 99%
“…The α-glucosidase inhibition assays were carried out according to the method described by Wang et al (2018b). Briefly, 5 µL of α-glucosidase solution (1.0 U/ mL), 20 µL of WSE, and 165 µL of sodium phosphate buffer (0.1 mM, pH 6.8) were mixed and incubated in a 96-well plate at 37°C for 10 min.…”
Section: α-Amylase and α-Glucosidase Inhibitory Activitiesmentioning
confidence: 99%
“…The severity of diabetes is normally proportional to the levels of cardiac cell death (Ghosh et al, ) and attenuation of apoptosis has shown amelioration of diabetic cardiomyopathy (Tian et al, ; Zhang et al, ). Various studies show the cardio‐protective effects of functional ingredients including protein hydrolysates from different food around the globe to possess cytoprotective effects against DM (Asokan et al, ; Chiang et al, ; Ramos‐Gomez et al, ; Wang et al, ). Irrespective of the effects of VHVV observed on STZ‐induced diabetic mice the tetra peptide showed effective attenuation of apoptosis in H9c2 induced by high glucose supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of diabetes is normally proportional to the levels of cardiac cell death (Ghosh et al, 2005) and attenuation of apoptosis has shown amelioration of diabetic cardiomyopathy (Tian et al, 2017;Zhang et al, 2017). Various studies show the cardio-protective effects of functional ingredients including protein hydrolysates from different food around the globe to possess cytoprotective effects against DM Chiang et al, 2014;Ramos-Gomez et al, 2017;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study of WHPs indicated that 3-10 kDa peptides reduced α-glucosidase activity and improved extracellular glucose consumption in HepG2 insulin-resistant cells. During in vivo tests, the WHPs decreased fasting blood glucose levels (64.82%) by improving liver glucokinase, glycogen and insulin secretion by 69.54%, 76.19%, and 23.71%, respectively [71]. A recent study by Barik et al confirmed the potential of anthocyanin-rich black currants (BC) to regulate hyperglycemia using CaCo-2 cells.…”
Section: Anti-diabetesmentioning
confidence: 93%